Implementasi Kebijakan Kurikulum Merdeka dalam Meningkatkan Capaian Hasil Belajar Mahasiswa Prodi Teknik Informatika Universitas Bhayangkara Surabaya - Armando, Yosea Bagus; Faizah, Dinar; Prawesti, Dhilla Adhika (ALSYS, 2023)
This research examines the implementation of the independent curriculum policy in improving student learning outcomes in the Informatics Engineering Study Program, Bhayangkara University, Surabaya. The research method used is qualitative, namely interviews and documentation, then the data is linked to the theory that has been obtained in lectures. Data was obtained by asking several question instruments to the head of the information engineering study program, Bhayangkara University, Surabaya. The results of the research show that in implementing the independent curriculum, especially in the information engineering study program at Bhayangkara University, Surabaya, they always try to provide the best in providing services in the form of educational services to students. Namely by providing facilities or infrastructure that are tailored to the study program's learning achievements, always communicating everything related to Independent Learning on the Independent Campus (MBKM) to students, providing training and competency development for educators and education staff, and providing continuous mentoring or supervision to students who are currently studying. did it mbkm. The implementation of the independent curriculum has had a positive impact not only on students who participate in MBKM but also on the image of the institution in the eyes of the public.